The first investigatons of cyanotoxins presence in waterbodies and watercources of Belarus - Mikheyeva, Tamara M. (Journal of the Belarusian State University. Ecology, 2021)
The estimation of species composition, abundance and biomass of cyanobacteria in “bloom” as well as the search for toxic species has been undertaken for the first time in 20 water bodies and water courses of Belarus mainly used for public recreation. There were identified 50 representatives of cyanobacteria assigned to 18 genera, among them three species were marked for the first time for the Belarus: Snowella atomus Komárek et Hindák., Anabaenopsis arnoldii Aptekar, Anabaenopsis kelifii Kog. By combining molecular-biological and analytical methods and by using genetic markers when studying toxic «water blooms» the search of genes responsible for synthesis of hepatotoxic microcystin, nodularin, cylindrospermosin and neurotoxic saxitoxin was undertaken. It has been shown that in all the investigated lakes and rivers there were cyanobacterium relating to Anabaena and Microcystis genera that can synthesize highly toxic microcystins – LR, RR, YR. Saxitoxin synthesis genes and close to it variants of paralytic toxins such as goniatoksins 5, 6, dekarbamoilgoniatoksin 2, dekarbamoilsaksitoksin and neosaksitoksin were found in 7 waterbodies.
Keywords: Belarus; water bodies and water courses; cyanobacteria; cyanotoxins